2019
DOI: 10.1002/ett.3672
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of full‐duplex cellular two‐way relay networks with the Nth worst relay selection under channel estimation error and cochannel interference

Abstract: This paper considers a full-duplex (FD) cellular multiuser two-way multirelay network, wherein one N a -antenna base station communicates bidirectionally with M single-antenna users via L single-antenna amplify-and-forward relays. A practical scenario where cochannel interference (CCI) and channel estimation error (CEE) present in the network is considered for the investigation.Considering the CEE and interferers at the relays, we formulate the Nth worst relay selection scheme, which consists the best relay se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Shukla et al 16,17 have investigated the effects of both co-channel interference (CCI) and channel estimation error (CEE) on the performance of cellular multiuser TWR system in which antenna selection at the relay, beamforming, and antenna selection at the base station have been employed. In Shukla et al, 17 the performance of FD-based cellular multiuser multi-relay TWR network has been evaluated with Nth worst relay selection under the combined effect of CEE and CCI. It has been demonstrated that the combined effect of CEE, CCI, and residual self-interference (RSI) extremely affects the achievable diversity order and even reduces it to zero.…”
Section: Introductionmentioning
confidence: 99%
“…Shukla et al 16,17 have investigated the effects of both co-channel interference (CCI) and channel estimation error (CEE) on the performance of cellular multiuser TWR system in which antenna selection at the relay, beamforming, and antenna selection at the base station have been employed. In Shukla et al, 17 the performance of FD-based cellular multiuser multi-relay TWR network has been evaluated with Nth worst relay selection under the combined effect of CEE and CCI. It has been demonstrated that the combined effect of CEE, CCI, and residual self-interference (RSI) extremely affects the achievable diversity order and even reduces it to zero.…”
Section: Introductionmentioning
confidence: 99%